Development and Characterization of Biointeractive Gelatin Wound Dressing Based on Extract of Punica granatum Linn - Marismar F. do Nascimento; Juliana C. Cardoso; Tarsizio S. Santos; Lívia A. Tavares; Tatiana N. Pashirova; Patricia Severino; Eliana B. Souto; Ricardo L. C. de Albuquerque-Junior (MDPI AG, 2020)
Punica granatum Linn (pomegranate) extracts have been proposed for wound healing due to their antimicrobial, antioxidant, and anti-inflammatory properties. In this work, we designed biointeractive membranes that contain standard extracts of P. granatum for the purpose of wound healing. The used standard extract contained 32.24 mg/g of gallic acid and 41.67 mg/g of ellagic acid, and it showed high antioxidant activity (the concentration of the extract that produces 50% scavenging (IC50) 1.715 µg/mL). Compared to the gelatin-based membranes (GEL), membranes containing P. granatum extracts (GELPG) presented a higher maximal tension (p = 0.021) and swelling index (p = 0.033) and lower water vapor permeability (p = 0.003). However, no difference was observed in the elongation and elastic modulus of the two types of membranes (p > 0.05). Our wound-healing assay showed that a GELPG-treated group experienced a significant increase compared to that of the control group in their wound contraction rates on days 3 (p < 0.01), 7 (p < 0.001), and on day 14 (p < 0.001). The GELPG membranes promoted major histological changes in the dynamics of wound healing, such as improvements in the formation of granular tissue, better collagen deposition and arrangement, and earlier development of cutaneous appendages. Our results suggest that a biointeractive gelatin-based membrane containing P. granatum extracts has a promising potential application for dressings that are used to treat wounds.